Development and Utilization of 3D Printed Material for Thoracotomy Simulation - Yates, Evan; Chirurgi, Roger; Adamakos, Frosso; Habal, Rania; Jaiswal, Rajnish; Kalantari, Hossein; Hassen, Getaw Worku (Emergency Medicine International, 2018)
Medical simulation is a widely used training modality that is particularly useful for procedures that are technically difficult or rare. The use of simulations for educational purposes has increased dramatically over the years, with most emergency medicine (EM) programs primarily using mannequin-based simulations to teach medical students and residents. As an alternative to using mannequin, we built a 3D printed models for practicing invasive procedures. Repeated simulations may help further increase comfort levels in performing an emergency department (ED) thoracotomy in particular, and perhaps this can be extrapolated to all invasive procedures. Using this model, a simulation training conducted with EM residents at an inner city teaching hospital showed improved confidence. A total of 21 residents participated in each of the three surveys [(1) initially, (2) after watching the educational video, and (3) after participating in the simulation]. Their comfort levels increased from baseline after watching the educational video (9.5%). The comfort level further improved from baseline after performing the hands on simulation (71.4%).